2017
DOI: 10.15406/jaccoa.2017.08.00330
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Prevalence and Associated Risk Factors of Post Dural Puncture Headache (PDPH) after Cesarean Section Delivery under Spinal Anesthesia

Abstract: Background: Post-Dural Puncture Headache (PDPH) is a common problem after a deliberate puncture of the dura-arachnoid for the purposes of diagnosis, therapy, spinal anesthesia, or unintentionally during epidural procedures. It is a clinically main complication which affects the daily life of patients with marked restriction of their physical activities. Spinal anesthesia is the frequent anesthetic procedure for obstetric patients which identified as cause for PDPH. The aim of the study was to assess the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
1
1
Order By: Relevance
“…This study found that women who had 2, 3, and >3 puncture attempts were, respectively, 8, 28, and 20 times more likely to develop PSH as compared to those who had 1 attempt. This is consistent with a study done in Cuba [ 20 ] and the one done by Tarekegn et al [ 4 ] in Ethiopia. The number of puncture attempts is a reflection of the magnitude of damage that is caused, resulting in more sites from which CSF is lost; therefore, fewer attempts result in a lower incidence of PSH.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study found that women who had 2, 3, and >3 puncture attempts were, respectively, 8, 28, and 20 times more likely to develop PSH as compared to those who had 1 attempt. This is consistent with a study done in Cuba [ 20 ] and the one done by Tarekegn et al [ 4 ] in Ethiopia. The number of puncture attempts is a reflection of the magnitude of damage that is caused, resulting in more sites from which CSF is lost; therefore, fewer attempts result in a lower incidence of PSH.…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of PSH in this current study is lower than 48.8% obtained in a study done by Nambooze et al [ 5 ] at Mulago National Referral Hospital Uganda, and 42.6% from the study done by Tarekegn et al [ 4 ] at Felege Hiwot Referral Hospital, Bahir Dar. This discrepancy may be attributed to the differences in preoperative hydration, study settings, and the size of the needle used in majority of cases.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation